Multi-Tissue Transcriptome Profiling of North American Derived Atlantic Salmon - Mohamed, Amin R.; King, Harry; Evans, Bradley; Reverter, Antonio; Kijas, James W. (Frontiers in Genetics, 2018)
The availability of a reference genome assembly for Atlantic salmon, Salmo salar, SNP genotyping platforms and low cost sequencing are enhancing the understanding of both life history and production-related traits in this important commercial species. We collected and analysed transcriptomes from selected tissues of Atlantic salmon to inform future functional and comparative genomics studies. Messenger RNA (mRNA) was isolated from pituitary gland, brain, ovary and liver before Illumina sequencing produced a total of 640 million 150-bp paired-end reads. Following read mapping, feature counting and normalization, cluster analysis identified genes highly expressed in a tissue-specific manner. We identified a cluster of 508 tissue specific genes for pituitary gland, 3395 for brain, 2939 for ovary and 539 for liver. Functional profiling identified gene clusters describing the unique functions of each tissue. Moreover, highly-expressed transcription factors (TFs) present in each tissue-specific gene cluster were identified. TFs belonging to homeobox and bhlh families were identified for pituitary gland, pou and zf-c2h2 families for brain, arid and zf-c2h2 for ovary and rxr-like family for liver. The data and analysis presented are relevant to the emerging Functional Annotation of All Salmonid Genomes (FAASG) initiative that is seeking to develop a detailed understanding of both salmonid evolution and the genomic elements that drive gene expression and regulation.